2005
DOI: 10.2337/diabetes.54.1.146
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like Peptide 1 Can Directly Protect the Heart Against Ischemia/Reperfusion Injury

Abstract: Glucagon-like peptide 1 (GLP-1), a gut incretin hormone that stimulates insulin secretion, also activates antiapoptotic signaling pathways such as phosphoinositide 3-kinase and mitogen-activated protein kinase in pancreatic and insulinoma cells. Since these kinases have been shown to protect against myocardial injury, we hypothesized that GLP-1 could directly protect the heart against such injury via these prosurvival signaling pathways. Both isolated perfused rat heart and whole animal models of ischemia/repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
418
4
17

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 565 publications
(462 citation statements)
references
References 38 publications
23
418
4
17
Order By: Relevance
“…Furthermore, cellular studies suggest that GLP-1 may activate cardioprotective and pro-survival pathways contributing to its beneficial effects. 15,16 More basic investigation and clinical studies are needed to confirm and advance this potentially important therapeutic approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cellular studies suggest that GLP-1 may activate cardioprotective and pro-survival pathways contributing to its beneficial effects. 15,16 More basic investigation and clinical studies are needed to confirm and advance this potentially important therapeutic approach.…”
Section: Resultsmentioning
confidence: 99%
“…Other laboratories have demonstrated similar salutary effects of GLP-1 in rodent models of myocardial infarction. Bose et al 16 showed that GLP-1 treatment reduced infarct size compared to control both In Vitro (26.7 ± 2.7% vs 58.7 ± 4.1%) and in vivo (20.0 ± 2.8% vs 44.3 ± 2.4%) in rat models of permanent coronary artery occlusion (35 minutes of ischemia followed by 120 minutes reperfusion). Taken together, these data suggest that GLP-1 has direct effects on post-ischemic myocardium, and the effects are mediated through the myocardial GLP-1 receptor.…”
Section: Experimental Studies Of Glp-1 In Myocardial Ischemiamentioning
confidence: 99%
“…29 Studies in animal models suggest beneficial effects of GLP-1 on atherogenesis, by inhibiting the inflammatory response in macrophages and endothelial adhesion 30 and modulating endothelial function. 31,32 Further cardioprotective effects, by means of increased coronary flow, 29 reduced myocardial infarct size, 33 and improved left ventricular function, have also been suggested by animal data. 30,34 Human mechanistic studies are consistent with these findings demonstrating an improvement in flow-mediated vasodilation in the postprandial state, 13 reduced infarct size in patients with ST-segment elevation myocardial infarction, 12,14 and an improvement in left ventricular ejection fraction in patients with heart failure.…”
Section: Discussionmentioning
confidence: 85%
“…24,33 In contrast to rodents, GLP-1 receptor expression on primate thyroid C-cells is very low, and no changes have been observed with in vitro stimulation of human C-cells by GLP-1 receptor agonists. 10,24 Patients with a personal or family history of medullary thyroid cancer or Multiple Endocrine Neoplasia type 2 (MEN2) will be excluded from ESXCEL.…”
Section: Safety Considerationsmentioning
confidence: 99%
“…Research has manipulated the biology of the entero-insular axis producing both injectable GLP-1 agonists that are used as an exogenous source of GLP-1 and oral DPP-4 inhibitors that shield the endogenous peptide from degradation [3]. Findings from our laboratory demonstrated for the first time that the administration of either GLP-1 native peptide or the DPP-4 inhibitor protects against myocardial IRI in the isolated rat heart model through a mechanism not driven by the stimulation of insulin secretion, but by the activation of intracellular prosurvival kinases cascades [4]. Subsequently, Lonborg et al showed that the infusion of exenatide, a GLP-1analogue, prior to primary percutaneous coronary intervention reduces myocardial infarct size patients presenting with ST-segment elevation myocardial infarction [5].…”
mentioning
confidence: 94%